Сравнительная эффективность использования протеиназ и цитокинов для определения выраженности воспалительного процесса при гиперплазиях эндометрия - Литвинова, С.В.; Коваленко, Е.П.; Фомочкина, И.И.; Кубышкин, А.В. (Таврический медико-биологический вестник, 2012)
Проведена порівняльна ефективність використання протеїназ та цитокінів для визначення вираженості запального процесу при гіперплазіях ендометрія. Встановлено, що про характер і міру вираженості запальних змін в ендометрії можна судити, як по рівню експресії CD45+, так і по рівню прозапальних цитокінів, неспецифічних протеїназ і їх інгібіторів в маткових змивах. При розвитку гіперплазії ендометрія відбувається підвищення рівнів ИЛ- 1β, ИЛ- 6, ФНО-α, зростання ЭПА і ТПА і зниження рівня КСІ. Зростання активності протеїназ і пригноблення активності місцевосинтезуємих кіслотостабільных інгібіторів, при гіперплазії ендометрія найбільш специфічно відбиває ступінь тяжкості запального процесу і може бути використане в якості місцевих маркерів для оцінки характеру запалення в ендометрії. Here we have presented the results of comparative efficiency of the proteinase-inhibitor activity and cytokines for determination of inflammation’s expression under endometrial hyperplasia. There was a strong correlation of an intensity of inflammatory changes with expression of CD45+, proinflammatory cytokines and non-specific proteinases and their inhibitors in cervico-vaginal washout fluids. We have found that development of endometrial hyperplasia accompanied by increase of interleukins, IL-1β and IL-6, as well as TNF-α, elastaseand trypsine-like proteinases activity, but decrease of the acid-stable inhibitors. Note that dynamic of these factors depends on type of the hyperproliferative process, and meantime reflects the feature of endometrial inflammation. In patients with endometrial hyperplasia the increase of proteinases activity together with depression of local synthesized acid-stable inhibitors are often correlated with the severity of inflammation and might be useful as a local inflammation’s markers.